A study of factors determining difficult surgery among patients undergoing laparoscopic cholecystectomy - Akhtar, Mohhamad Sadik; Alam, Parwez; Alvi, Yasir; Ali Rizvi, Syed Amjad; Raza, Mohhmad Habib (International Surgery Journal, 2019)
Background: With widespread use of laparoscopic cholecystectomy and its applicability in many difficult situation, the chances of complication and difficulty during surgery have increased. This study was done to determine the factors which could preoperatively predict difficulty undergoing laparoscopic cholecystectomy. Methods: The data were obtained from the patients admitted to in wards of General Surgery, JN Medical Collage, Aligarh Muslim University, and Aligarh, India undergoing laparoscopic cholecystectomy. The difficult laparoscopic cholecystectomy was defined as procedures exceeded 70 minutes in duration or those which were converted to open procedure. Dependent variable included demographic factors, clinical and sonographic findings. P value was kept at 0.05. Results: During the study duration, 200 patients were included in the study undergoing for the laparoscopic cholecystectomy and out of this 85 had difficult outcome procedure. High BMI, hypertension, previous upper abdomen surgery, deranges AST and serum creatinine along sonographic findings of gall balder wall thickening and pericholecytsic edema were found to be significantly associated with difficult LC. Conclusions: This study demonstrates that presence of various factors can predict the difficult outcome of laparoscopic cholecystectomy. This can help in minimizing the complication and council the patients regarding difficult procedure and need for conversion to open cholecystectomy, especially relevant for funds-limited settings like India.